Grades for glory? The impact of grade appeasement on business school teacher evaluations - Villagrasa, Jorge; Donaldson, Colin; Soler, Ángel (Journal of Management and Business Education, 2024)
Educational institutions have had the pending task of knowing what really happens in their classrooms, which professors make a real difference, which students would need help to improve their performance, and even more importantly, how to manage the enormous amount of information gathered each year. To address this problem, in this paper we propose the use of retrospective data from 210 undergraduate courses in Spain, which equals 1,320 European credits, 10,500 students, and four complete academic years (18/19, 19/20, 20/21, 21/22) to generate a monitoring tool or automatic dashboard with which to try to optimize the operation of such institutions and help them to make (even more) optimal decisions. To do this, all courses were grouped into ten typologies or categories: (1) if they were 'soft skills'/'hard skills' courses, (2) if they were taught in the 1st, 2nd, 3rd or 4th academic year, (3) if the professor was male or female, (4) whether the course was taught in English or not, (5) whether the professor was internal and permanent staff of the university or an associate professor with a temporary contractual relationship with the institution, (6) whether his/her main professional activity was teaching, therefore being more academic-oriented or this was rather a hobby and a complementary professional activity, therefore being more practical-oriented, (7) their age, (8) if several professors shared the course or only one taught it, (9) if it was a semester or annual course, (10) and if it was taught during the Covid-19 period or outside of it. Our results show that, despite the existence of numerous types of methodologies to achieve the desired student motivation, there would only be one category that would generate significant differences in the grades of the students: if they were ‘soft skills’/’hard skills’ courses. However, on the contrary, there would be much more types of courses (and professors) which would affect the preferences and valuation of the student to the teaching received (and effectively paid by him/her). That is, despite reaching the same academic results, students do value one type of professors better than others. Likewise, through this work it is intended to demonstrate the non-existence of the "false belief" that better evaluations received by professors are since they give higher grades to their students, regardless of its dispersion. In this way, it is intended to prevent possible atypical behaviors by professors. Thus, this paper gives light to (re)consider which variables should actually matter in educational institutions, analyzing its teaching-learning processes, management and even the retention of its key players.